Will The Employees of DJP Leave Their Jobs Due to Job Rotation Policy?: The Roles of Job Stress and Gender - Angga Sekensend; Syahrizal Syahrizal (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to examine the effect of job rotation on job stress and turnover intention based on transactional stress theory, while also analyzing the mediating role of job stress and the moderating role of gender. The study involved 180 employees of the Directorate General of Taxes who had experienced at least three job rotations, using questionnaires distributed directly and online. Data were analyzed using PLS-SEM. The findings show that job rotation policies significantly influence job stress and turnover intention. Job stress mediates the relationship between job rotation and employees’ intention to leave. Female employees tend to experience higher job stress when transferred compared to male employees. Both male and female employees are more likely to consider leaving their jobs when job rotation and job stress are high. This research highlights transactional stress theory as an appropriate framework to explain the pathway from job rotation to job stress and turnover intention, filling a gap in previous studies that rarely examined this relationship from this perspective. The study also contributes by analyzing gender as a moderating variable. Practically, organizations should avoid implementing frequent rotation policies and should consider exceptions for female employees to minimize job stress and prevent turnover.